MENTAL HEALTH CARE FOR INDIVIDUALS WITH ANTISOCIAL PERSONALITY DISORDER: AN INTEGRATIVE REVIEW - Novais, Lara Vitória Luppi; de Sá, Silvio Vieira; Paiano, Marcelle; Rodrigues, Thamires Fernandes Cardoso da Silva; Frez, Flávia Cristina Vieira; Zulin, Aline; Uema, Roberta Tognollo Borotta; Back, Ivi Ribeiro; Cardoso, Luana Cristina Bellini (Seven Editora, 2025)
This study conducts a systematic review of the literature on mental health care for individuals with antisocial personality disorder. This is, characterized by a persistent pattern of disregard for the rights of others and violation of social norms, presents significant challenges for treatment due to comorbidity with other disorders, resistance to treatment, and social stigma. The review highlights the complexity of managing antisocial personality disorder and the need for specific therapeutic approaches. Programs such as Systems Training for Emotional Predictability and Problem Solving and psychoeducation have shown potential for reducing symptoms and increasing treatment adherence. Additionally, mentalization-based therapy and pharmacotherapy, with the use of medications such as inhaled loxapine, emerge as promising therapeutic tools. However, the literature points to the need for more research and greater investment in training healthcare professionals. Integrating scientific evidence into clinical practice is essential to optimize care for these patients and reduce the impact of antisocial personality disorder on the lives of individuals and society.DOI: https://doi.org/10.56238/sevened2025.036-150